VALUE ADDED FERTILIZERS AMELIORATE GRAIN YIELD AND NUTRITIONAL QUALITY OF MAIZE CROP - Z. Ali; M.Akram; M.A.Ali; M.Shoaib; M.Y.Khurshid; J.Iqbal; S.S.HShah; A.Khan; A.Khan; A.Mehboob (Pakistan Journal of Science, 2023)
A field trial was conducted to gauge the impact of value added NPK fertilizer, Zarkhez Plus, (N:08%;P:23%; K;18%) and biologically activated Zinc coated Urea (BAZU) maize. Treatments consisted; Control (T1), Straight Fertilizers (DAP, MoP, Urea) (T2), Zarkhez Plus + BAZU as 1/3rd replacement of Urea (T3), Zarkhez Plus + BAZU as 2/3rd replacement of Urea (T4), and Zarkhez Plus + BAZU as 1/3rd replacement of Urea (T5). Results suggested that plant height, stem girth, rows cob-1, grains row-1, grains cob-1, thousand seed weight were significantly improved by the application of Zarkhez Plus and BAZU. Grain yield was increased upto 30% with the application of Zarkhez Plus and BAZU compared to straight fertilizers. Application of BAZU beyond 1/3rd of the total N requirement did not increase the grain yield significantly but improved grain quality with higher Zn and K contents. Maize grain yield can be significantly increased with the application of Zerkhez Plus and replacing 1/3rd in-season N requirement with BAZU.